Personality Traits and Digital Wellbeing: Work Life Balance as a Mediator - Puteri Nur Diana Sari Choirudin; Eko April Ariyanto; Amanda Pasca Rini (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The increasing reliance on digital technology has reshaped work practices, particularly among digital workers, raising concern about digital wellbeing. Ths study investigates the relationship between personality traits and digital wellbeing, with work life balance as a mediating variable. A quantitative correlational approach was applied to Generation Z digital workers in Surabaya. Data were colledted using Likert-scale instruments and analyzed through Sctructural Equating Modeling Partial Least Squares (SEM-PLS) with SmartPLS 4.1.1.6. The Result demonstrate that personality traits significantly influence digital wellbeing and work life balance. Work life balance also shows a significant effect on digital wellbeing and mediates the relationship between personality traits and digital wellbeing. These findings highlight the importance of work life balance as a key psychological mechanism in explaining how individual personality characteristics shape digital wellbeing in digitally intensive work contexts